2006
DOI: 10.1111/j.1540-4781.2006.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Depth of Vocabulary Knowledge and L2 Learners’ Lexical Inferencing Strategy Use and Success

Abstract: The editors of both journals hope their readers will find this sharing of scholarship interesting and beneficial.This study examines the relationship between English as a second language (ESL) learners' depth of vocabulary knowledge, their lexical inferencing strategy use, and their success in deriving word meaning from context. Participants read a passage containing 10 unknown words and attempted to derive the meanings of the unknown words from context. Introspective thinkaloud protocols were used to discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
154
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(180 citation statements)
references
References 47 publications
14
154
0
5
Order By: Relevance
“…The findings are in line with the idea put forward by Nassaji (2006) that learners rely on certain modalities for facing the challenges as they are tackled through their inherent learning styles. Such individual differences give learners adequate knowledge and strategies to make use of contextual and extra-contextual clues in inferencing.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The findings are in line with the idea put forward by Nassaji (2006) that learners rely on certain modalities for facing the challenges as they are tackled through their inherent learning styles. Such individual differences give learners adequate knowledge and strategies to make use of contextual and extra-contextual clues in inferencing.…”
Section: Resultssupporting
confidence: 76%
“…Nassaji (2006) defines inferencing as the attempts made by readers to extract meaning from a text. As a cognitive activity involved in the act of reading comprehension both in L1 and L2, inferencing is achieved through various strategies ranging from establishing connections between different parts of text and linking the text with background knowledge to looking for cohesion and coherence within the text as well as making informed guesses about the unfamiliar vocabulary items.…”
Section: Introductionmentioning
confidence: 99%
“…Qian (1999) showed that this test has a high degree of internal reliability. The reliability of the test as reported by Read is 0.93 and by Qian (1998Qian ( , 2002 and Nassaji (2004) above 0.90. Different studies make clear that the test, moreover, having a high degree of correlation with the size of vocabulary knowledge, is closely correlated with L2 reading comprehension ability.…”
Section: Word Associates Test (Wat)mentioning
confidence: 86%
“…Several tools were proposed for measuring this dimension of vocabulary knowledge (sWesche & Paribakht, 1996) but one the most frequent used measure according to Nassaji (2004) to appraise the size of vocabulary knowledge is Vocabulary Levels Test (VLT).…”
Section: Depth Vs Breadth Dimensions Of Word Knowledgementioning
confidence: 99%
“…Schmitt, 1997), others focused on particular strategies, such as guessing the meaning from context and using dictionaries (e.g. Nassaji, 2006;Chen & Truscott, 2010). Examining VLSs aim to help learners to be autonomous in their vocabulary learning and make them less reliant on teachers.…”
Section: Vocabulary Learning In the Classroommentioning
confidence: 99%